Analisis Yuridis Terhadap Pengelolaan Investasi Pada Perusahaan Asuransi Jiwa - Dasuki Santoso; Helvis Helvis; Markoni Markoni (CV. Syntax Corporation Indonesia, 2022)
The problem of this research is how to manage the investment made by the company PT. Asuransi Jiwasraya (Persero) according to the applicable Financial Services Authority (POJK) Regulations and the role of the state in providing legal certainty guarantees to customers of PT. Asuransi Jiwasraya (Persero). This research uses normative juridical and empirical juridical research methods with reference to legal norms in legislation and investment management by the Jiwasraya Insurance company. This research is analytical descriptive by describing the investment management that is carried out and that occurs in the Jiwasraya Insurance company, which is associated with theory, practice, and applicable laws and regulations. With this research, it is hoped that the Financial Services Authority as a regulator will reform the insurance industry. This can cause problems, namely: First, what is the meaning of gambling and betting in the field of Limited Liability Company business; Second, whether the regulation of gambling and betting related to the line of business of the Limited Liability Company does not conflict with the principle of legal certainty; Third, what are the future arrangements so that the Notary deed regarding the establishment of a Limited Liability Company in the field of gambling and betting business does not conflict with the principle of legal certainty. This research is a normative juridical research. The results of this study conclude that First, gambling and betting is a game of chance by risking an uncertain amount of money. The gambling and betting business sector carried out by the Limited Liability Company occurs because of the will of the founder of the Limited Liability Company and the opportunity to play gambling which can be used as a livelihood. If the Limited Liability Company is in default, the gambling player cannot claim his rights. Second, the regulation of the gambling and betting business sector in the Central Statistics Agency Regulation No. 2 of 2020 concerning the Standard Classification of Indonesian Business Fields (KBLI) is contrary to the principle of legal certainty because it does not pay attention to special provisions governing gambling and betting and does not reflect the values ​​of Pancasila and the 1945 Constitution. Third, future arrangements for the gambling business sector and betting must pay attention to 3 (three) legal objectives, namely justice, benefit and legal certainty by eliminating the gambling and betting business sector in the KBLI and there must be a regulation on the determination of the existing business fields in the KBLI.